Tailoring the Charge/Discharge Potentials and Electrochemical Performance of SnO2 Lithium‐Ion Anodes by Transition Metal Co‐Doping. Issue 3 (3rd January 2020) - Birrozzi, Adele; Asenbauer, Jakob; Ashton, Thomas E.; Groves, Alexandra R.; Geiger, Dorin; Kaiser, Ute; Darr, Jawwad A.; Bresser, Dominic
Abstract: It has been shown that the introduction of several transition metal (TM) dopants into SnO2 lithium‐ion battery anodes can overcome the issues associated with the irreversible capacity loss from the conversion reaction of SnO2 and the aggregation of the metallic Sn particles formed upon lithiation. As the choice of the single dopant, however, plays a decisive role for the achievable energy density – precisely its redox potential – we investigate herein TM co‐doped SnO2, prepared by using a readily scalable continuous hydrothermal flow synthesis (CHFS) process, to tailor the dis‐/charge profile and by this the energy density. It is shown that the judicious choice of different elemental doping combinations in samples made via CHFS simultaneously improves the cycling performance and the full‐cell energy density. To support these findings, we realized a lithium‐ion full‐cell incorporating the best performing co‐doped SnO2 as negative electrode and high‐voltage LiNi0.5 Mn1.5 O4 (LNMO) as positive electrode–to the best of our knowledge, the first full‐cell based on such anode material in combination with LNMO as cathode active material. Abstract : Choosing the right dopant : Transition metal co‐doping of nanoparticulate SnO2, prepared using a readily scalable continuous hydrothermal flow synthesis process, allows for tailoring the dis‐/charge profile of such material when employed as potential lithium‐ion anode and, thus, enhanced full‐cell energy densities and long‐term cycling stability. The advantageous effect is confirmed also by realizing high‐energy lithium‐ion full‐cells comprising the best‐performing co‐doped SnO2 as anode and high‐voltage LiNi0.5 Mn1.5 O4 cathodes.